The Effects Of Politeness Principle In A Multimedia Courseware On Achievement And Emotion Of Students With Different Ability - Hurmuzan, Shuhaila (2020)
The best design practices are essential to be embedded into designing and developing the strategies of any subject content to promote students’ learning. This study aims to examine the effects of politeness principle in multimedia with coaching as an instructional strategy on student achievement and emotion of learning on the ICT sub-topic – Developing Non-linear Interactive Multimedia Presentation. The politeness principle is essentially the result of studies based on Brown and Levinson's politeness theory. The first part is to design and develop a multimedia learning courseware that is intended to deliver the chosen topic with two different treatment approaches. The final part of this study is to investigate the effects of the two different treatment approaches among students with different ability on their achievement and emotion towards the learning material